Influence of particle size on gas-adsorption experiments of shales: An example from a Longmaxi Shale sample from the Sichuan Basin, China. (15th December 2016) - Han, Hui; Cao, Yan; Chen, Shi-jia; Lu, Jun-gang; Huang, Cai-xia; Zhu, Hai-hua; Zhan, Pan; Gao, Yuan
Highlights: Low-pressure CO2 and N2 gas adsorption experiments were performed on shale samples with particle sizes from 4 to 0.058 mm. The influence of particle size on low-pressure CO2 and N2 gas adsorption experiments of shales was analyzed. A particle size of 0.113 mm (130 mesh) is optimum for shale samples used in low-pressure CO2 and N2 adsorption experiments. Abstract: To explore the optimum particle size range for low-pressure gas adsorption experiments of shales, a sample of the Longmaxi shale from the Sichuan Basin, China, was crushed into various particle sizes between 4 and 0.058 mm. Low-pressure CO2 and N2 adsorption experiments were then performed on these crushed samples, and the pore volume, surface area, and pore size distribution (PSD) were determined from isotherms of gas adsorption. Variations in the volume of sorbed gas, pore volume, surface area, and PSD were recorded across the two series of experiments. In the CO2 adsorption experiments, in which particle size ranged from 4 to 0.83 mm, sorbed gas volume, pore volume, and surface area increased with decreasing particle size. No obvious changes were found in sorbed volume, pore volume, surface area, or PSD for the samples with particle sizes from 0.83 to 0.058 mm. In the N2 adsorption experiments, the sorbed gas volume and surface area increased with decreasing particle size in samples from 4 to 0.113 mm, whereas no obvious variations were observed in the 0.113–0.058 mm samples. Similarly, pore volume and PSD showed clear changes with decreasing particle size for the 4–0.113 mm samples. The results show that 0.113 mm (130 mesh) is the optimum particle size for low-pressure CO2 and N2 adsorption experiments that seek to analyze the characteristics of shale reservoirs.